Problematika Minimnya Pencatatan Perkawinan di Wilayah Kantor Urusan Agama (KUA) Distrik Arso Kabupaten Keerom - Anam, Mohammad Irsad Abdul; Al Abza, M. Thohar; Wahib, Moh. (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2024)
Marriage registration is marriage administration based on statutory regulations to provide legal protection and certainty for the marriage. This research aims to find out "why there are still unregistered marriages in the jurisdiction of the Arso District Religious Affairs Office". Data was obtained directly from the community as the first source by conducting field research using observation, interviews and documentation. The results of this research show that the lack of registration of marriages that occur in the jurisdiction of the KUA Arso District is caused by several factors, including (1) the community's lack of understanding of Islamic law; (2) KUA, which has quite a long distance to travel, (3) several transmigrant communities still do not have official residence documents; (4) some people think that the most important thing is that the marriage is valid religiously without needing to be registered with the KUA; and (5) they register their marriage when they need a marriage book due to population administration needs, such as making a family card and child's birth certificate, as a requirement for their child's schooling.